Arbuscular mycorrhizal fungi on the development and productivity of grain sorghum cultivars - Canepelle, Eduardo; Ferreira da Silva, Rodrigo; da Rocha Giovenardi, Andréa; Bonini da Luz, Felipe; da Silva, Ana Paula; Barros, Sinara (Revista Ciência Agronômica, 2024)
Arbuscular mycorrhizal fungi increase water and nutrient absorption from the soil by plants. However, its benefits to plants vary depending on the inoculated species. This study aimed to determine the influence of different species of mycorrhizal fungi on the development and productivity of grain sorghum cultivars. The experiment was conducted in a greenhouse in a completely randomized design in a 2 x 5 factorial scheme, consisting of two sorghum cultivars (BRS 310 and BRS 330) and five treatments (control without inoculation and four species of arbuscular mycorrhizal fungi: Gigaspora margarita, Glomus formosanum, Acaulospora scrobiculata, and Scutellospora pellucida), with four replications. Plant height, stem diameter, leaf area, length, volume, specific surface area, root diameter, shoot dry mass, root dry mass, thousand-grain weight, grain productivity, colonization, dependence, and mycorrhizal efficiency were evaluated. The results showed that inoculation with the species S. pellucida induced higher root and shoot development of plants of the cultivar BRS 310, as well as higher productivity of sorghum grains. The cultivar BRS 330 showed higher root development when inoculated with the species G. formosanum and a higher shoot development when inoculated with the species A. scrobiculata. Mycorrhizal dependence for grain productivity was low and varied with the inoculated species of mycorrhizal fungi. The mycorrhizal efficiency for shoot dry mass was higher with the inoculation of A. scrobiculata and S. pellucida in the cultivar BRS 310 and A. scrobiculata and G. margarita in the cultivar BRS 330.